The impact of desilication product on bauxite residue flocculation - Senaputra, A.; Fawell, Phillip; Jones, Franca; Smith, P. (AQW Incorporated, 2012)
The pre-desilication step within the Bayer Process seeks to transform reactive silica in bauxite into desilication product (DSP) prior to digestion, thereby reducing post-digestion precipitation and scaling. The precipitated DSP is removed with the other residue phases in the primary settling stage. While the proportion of DSP within the residue can be significant, there are surprisingly few open-literature studies that consider the impact of DSP on residue flocculation and settling. Such studies typically involve bauxites of a fixed composition, which limits the scope to vary residue properties while investigating flocculation mechanisms. In this study, DSP has been formed from the reaction of standard kaolin in synthetic Bayer liquor in the presence of iron oxides. Variation of the reaction conditions (temperature, duration, kaolin to iron oxide ratio) has produced a range of synthetic residue slurries that have been characterised in terms of their physical and flocculation properties. Effective comparison of the latter could only be achieved after detailed optimisation of test conditions, which included (i) slurry stability over time, (ii) solids concentration, (iii) temperature and concentration of the dosed flocculant, and (iv) flocculant make-up/shelf life. The detrimental impact of DSP is clearly reflected in lower settling rates, higher supernatant solids and poor consolidation over a range of solid densities and DSP contents of operational interest. Flocculant dosage response curves are also less steep and shifted towards higher demand. A number of flocculants are contrasted in terms of their suitability for high DSP residues, with the practical implications of their application discussed.